1987
DOI: 10.1042/bj2470707
|View full text |Cite
|
Sign up to set email alerts
|

Structure-activity relationships of 4-hydroxyalkenals in the conjugation catalysed by mammalian glutathione transferases

Abstract: The substrate specificities of 15 cytosolic glutathione transferases from rat, mouse and man have been explored by use of a homologous series of 4-hydroxyalkenals, extending from 4-hydroxypentenal to 4-hydroxypentadecenal. Rat glutathione transferase 8-8 is exceptionally active with the whole range of 4-hydroxyalkenals, from C5 to C15. Rat transferase 1-1, although more than 10-fold less efficient than transferase 8-8, is the second most active transferase with the longest chain length substrates. Other enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
73
0
2

Year Published

1991
1991
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(83 citation statements)
references
References 30 publications
8
73
0
2
Order By: Relevance
“…Furthermore, since substrate recognition at the H-site is mediated primarily by hydrophobic interactions, binding at this site is expected, within the steric limitations of each gene class H-site, to be less constrained, thus giving it the flexibility required to accommodate a range of structurally different hydrophobic substrates. Structure/activity investigations, exploring the significance of hydrophobic interactions at the H-site, indicate that cytosolic glutathione S-transferases generally exhibit increased binding affinities in response to increased hydrophobicity of 4-hydroxyalkenal substrates [116] and of the alkyl group in S-alkylated glutathione competitive inhibitors [117].…”
Section: H-site and The Binding Of Electrophilesmentioning
confidence: 99%
“…Furthermore, since substrate recognition at the H-site is mediated primarily by hydrophobic interactions, binding at this site is expected, within the steric limitations of each gene class H-site, to be less constrained, thus giving it the flexibility required to accommodate a range of structurally different hydrophobic substrates. Structure/activity investigations, exploring the significance of hydrophobic interactions at the H-site, indicate that cytosolic glutathione S-transferases generally exhibit increased binding affinities in response to increased hydrophobicity of 4-hydroxyalkenal substrates [116] and of the alkyl group in S-alkylated glutathione competitive inhibitors [117].…”
Section: H-site and The Binding Of Electrophilesmentioning
confidence: 99%
“…However, the reported ability of HNE to modify proteins and therefore influence enzymatic activity, led us to study the possibility of a direct interaction between HNE and GSHPx. HNE reacts with GSH spontaneously, but within cells this reaction proceeds at a much higher rate, catalyzed by specific isoforms of GSH S-transferases (66,67). Moreover, reaction of this aldehyde with other aminoacid residues leads to the modification of proteins and eventually to the inactivation of their enzymatic activity.…”
Section: -Hydroxynonenal Inhibits Gshpxmentioning
confidence: 99%
“…The function of rGST 8-8 has not been elucidated in the brain regions where we have detected differential expression, and these brain regions are known to be important in the brain reward pathway. Because GSTs are multifunctional proteins that are involved in transport and biosynthesis of endogenous compounds and play a defensive role against oxidative damage as well as neuroprotection (Danielson et al, 1987;Hubatsch et al, 1998;Singhal et al, 1994), they could be playing a role in these rat brain regions that has yet to be discovered. It has been shown that alcohol exposure alters the glutathione/glutathione transferase (Schnellmann et al, 1984) and the glutathione/glutathione peroxidase-1 systems (Bailey et al, 2001) in response to ethanol-related oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Author Manuscript (Bjornestedt et al, 1995;Danielson et al, 1987). Because the GST 8-8 designation is widely used in the literature, this nomenclature is used throughout this article.…”
Section: Author Manuscript Author Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation